Apolipoprotein Fusion Enables Spontaneous Functionalization of mRNA Lipid Nanoparticles with Antibody for Targeted Cancer Therapy - Park, Wonbeom; Choi, Jiwoong; Hwang, Jaehyeon; Kim, Suhyun; Kim, Yelee; Shim, Man Kyu; Park, Wooram; Yu, Seokhyeon; Jung, Sangwon; Yang, Yoosoo; Kweon, Dae-Hyuk (American Chemical Society, 2025)
The mRNA-lipid nanoparticles (mRNA@LNPs) offer a novel opportunity to treat targets previously considered undruggable. Although antibody conjugation is crucial for enhancing the specificity, delivery efficiency, and minimizing the toxicity of mRNA therapeutics, current chemical conjugation methods are complex and produce heterogeneous particles with misoriented antibodies. In this work, we introduce a chemical-free approach to functionalize mRNA@LNPs with antibodies, mimicking protein corona formation for targeted mRNA delivery. By fusing apolipoprotein to the Fc domain of a targeting antibody, we enabled the antibody to spontaneously display on the surface of mRNA@LNPs without altering the existing LNP process or employing complex chemical conjugation techniques. We demonstrated precise protein expression using trastuzumab-bound mRNA@LNPs, facilitating specific mRNA expression in HER2-positive cancer cells. mRNA was efficiently delivered to the tumor site after intravenous administration. While the control LNPs lacking targeting antibodies caused acute liver toxicity, trastuzumab-displayed LNPs showed no systemic toxicity. The tumor-specific delivery of p53 tumor suppressor mRNA led to the complete regression of cancer cells. Thus, apolipoprotein fusion enables a straightforward and scalable production of antibody-functionalized mRNA@LNPs, offering significant therapeutic potential in gene therapy.